Natural Hazards and Disasters [2 volumes] : From Avalanches and Climate Change to Water Spouts and Wildfires [2 volumes] /: From Avalanches and Climate Change to Water Spouts and Wildfires [2 volumes]. (2020) - Unknown
No abstract available